Attempts at diffusion of Saint-Simon's ideas and their application in the Greek territory between 1825-1837 - Μπαλόγλου, Χρήστος Π. (SPOUDAI Journal of Economics and Business, 2003)
The purpose of this paper is to bring to light that specific persons occupied to tranfer into the Greek era the ideas of Saint-Simon, after his death in 1825. Saint-Simon's name and doctrines were known to the Greek scholars of the Diaspora and especially to Corais' circle. One of the most active Corais' disciples, Fr. Pylarinos (1802-1882) adopted the doctrines of the Saint-Simonists and propagated and presented them in the above newspaper "Helios". In 1833, when King Otho came to Greece, a group of Saint-Simonists fugitives ahead by Gustave Eichthal took shelter in Nafplion. Eichthal proposed the establishment of the "Bureau of Public Finance", inspired by Saint-Simon's idea of a foundation of a "chambre d'industrie", which would play an advisory role in the Ministry of Commerce, as Saint-Simon described in his "De systeme industriel" (1821). The Saint-Simonists, as members of a sort of planning board were to constitute a managerial elite and assume the direction of the economy, transforming the anarchy of production into an organization of production. They believed that they found in the new established Greece the ideal field for the application of Saint-Simon's ideas. Despite the fact that the "Bureau of Public Finance" had an ambitious beginning, it was not as fruitful as expected. The main reasons for this could have been the insufficiency in personnel, but mainly, the political status of the country, which did not permit the intervention in a social-economic structure which was already difficult. JEL Classification: B11, B12